New insights into the influences of baking and storage on the nonvolatile compounds in oolong tea: A nontargeted and targeted metabolomics study. (1st May 2022) - Peng, Jiakun; Dai, Weidong; Lu, Meiling; Yan, Yongquan; Zhang, Yue; Chen, Dan; Wu, Wenliang; Gao, Jianjian; Dong, Minghua; Lin, Zhi
Highlights: A comprehensive metabolomics study on Foshou oolong teas of different scent types. 92 differential compounds were identified among fresh-, strong- and aged-scent types. Baking reduced cis -flavanols through degradation, epimerization and interaction with theanine. Storage reduced cis -flavanols through degradation and interaction with theanine. Simulated reaction elucidated pathways of EPSFs and apigenin C-glycosides increases. Abstract: A nontargeted and targeted metabolomics method was applied to comprehensively investigate the influences of baking and storage on chemical constituents in fresh-, strong-, and aged-scent types of Foshou oolong teas. The contents of N -ethyl-2-pyrrolidone-substituted flavanols (EPSFs), flavone C-glycosides, gallic acid, and most lipids increased after baking and storage, while the contents of cis -flavanols, alkaloids, flavonol O-glycosides, and most amino acids decreased. Degradation, epimerization, and interaction with theanine were main pathways for the decrease in cis -flavanols. Approximately 20.7%, 12.8%, and 11.6% of epigallocatechin gallate were degraded, epimerized, and interacted with theanine after baking, respectively; 22.5% and 8.71% of epigallocatechin gallate were degraded and interacted with theanine after 10-year storage, respectively. Simulated reactions confirmed that the increases in EPSFs and apigenin C-glycosides were caused by interactions between theanine and flavanols and between apigenin aglycone and glucose, respectively. This study offers novel insights into chemical changes during baking and storage of oolong tea.